2018
DOI: 10.1155/2018/2302407
|View full text |Cite
|
Sign up to set email alerts
|

The Tribological and Sealing Properties of PFA Composites

Abstract: The polytetrafluoroethylene (PTFE) and perfluoroalkoxyperfluoropropyl vinyl ether (PFA) composites were prepared using carbon fiber (CF) and glass fiber (GF) as fillers. The effects of these fillers on the tribological and sealing properties were investigated. The tribological and sealing properties of the composites were evaluated by a wear tester and a seal test rig. Results showed that the incorporation of CF and GF both improved the wear resistance with composites, approaching wear rates as low as 10−6 mm3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this regard, nanometric dispersion fillers are quite effective, which have an uncompensated charge and form orderly "quasi-crystalline" areas in the volume of the composite [26,27].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In this regard, nanometric dispersion fillers are quite effective, which have an uncompensated charge and form orderly "quasi-crystalline" areas in the volume of the composite [26,27].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Many researchers have tested other polymers as potential replacements. Yu et al 16 found that PFA/CF composites have optimal wear resistance and sealing properties. Mazza et al 17 investigated the tribological behavior of epolytetrafluoroethylene-based composite material filled with Valflon F115, which showed lower coefficient of friction than unfilled PTFE.…”
Section: Introductionmentioning
confidence: 99%